The organisational effects of installing a distributed processing system - Lay, Peter Mark Quine (University of Cape Town, 2016)
Bibliography: 238-248. === Since its introduction to business in 1952, computerised data processing has undergone a number of substantial changes, both in the hardware and the techniques that are used. The introduction of miniaturisation, and the resultant lowering of the costs of circuitry, has led to the widespread use of mini- and micro-computers. There has also been a large increase in the use of communication facilities. Initially, almost all organisations centralised their computer facilities at the Head Office and systems were run in the batch mode. The need to service the requirements of remote users was resolved by installing on-line facilities and providing unintelligent terminals to those users. Alternatively, stand-alone computers were installed at the remote locations. However, the requirements of businesses for centralised reporting and control led to the need to install processing units at the user sites and to connect those computers, via communications links, to a computer facility located at Head Office. In this way distributed data processing evolved. The provision of this type of processing mode has important implications to the organisation in such areas as costs, staffing, planning, control and systems design. This thesis, therefore, investigates the current (1980) trends in relation to distributed processing. It specifically examines the developments in hardware, software, and data communications. It assesses the criteria that should be considered by an organisation in selecting either the centralisation or distribution of its processing facilities. Through a field study both successful and unsuccessful distributed installations are examined. Conclusions are then drawn and recommendations made, to provide management with working guidelines when assessing the feasibility and practicality of distributed processing for its organisation. The findings of the study are appropriate for both general management and DP management with only centralised computing experience; and for individuals offering professional computer consultancy services to existing or potential users.